(3fWGb JWHjb bhGfjf ecGaMI GdEQgGH ef MjK GdecGf (B: s (3OQGSI ebGQfI (B/ s - (3jGSQ eUWai efUhQ GdHjhejs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JJfGhd GdOQGSI GdCQcGf GdYGeI ddLQjeI GdEQgGHjI h jJfGhd GdLQjeI GdEQgGHjI GdJGeI ef NdGd KdGK eWGdH GdChd jJVef GdTQW GdeaJQV hLhO eTQhY ELQGej h GdKGfj jJfGhd GdQcf GdeGOj dLQGFe GdEQgGH (B- (3GdSdhc GdeGOj h GdfJjLI h YdGbI GdSHHjI ddLQjeI GdEQgGHjI h GdKGdK jJVef GdQcf GdeYfhj ddLQjeI GdEQgGHjI Ke JfGhd GdeHGOF GdJj JMce JWHjb bhGfjf ecGaMI GdEQgGH ef MjK GdecGf s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B127-138s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3CQcGf GdLQjeI s; (3GdEQgGH s; (3GdJTQjYGJ GdLfGFjI s; (3GdWGHY GdJfXjej ddSdhc GdEQgGHjs; (3GdNWQs; (3bGfhf ecGaMI GdLQGFe GdEQgGHjI GdEeGQGJjs; (3GdJQhjYs; (3eHOC GbdjejI GdfU GdLfGFj ddLQjeI GdEQgGHjIs; (3GdLQGFe GdJi JbY Ydi GdSafs; (3eHOC YGdejI GdfU GdLfGFj s; (3fXQjI GdaYds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs